Forgotten Elastic Band as an Unusual Cause of Limb Ulceration: Case Report and Review of the Literature. (14th July 2019) - Werner-Gibbings, Keagan; Ischia, Liesl; Khoma, Oleksandr; Tang, Robert
Abstract : We discuss a case of circumferential ulceration of the lower leg in a cognitively impaired elderly man with poor tissue integrity. Thorough clinical examination eventually determined the cause as being a circumferentially placed, forgotten elastic band causing ulceration via sustained tension around the limb. Circumferential application of an elastic band to an extremity is an exceedingly rare but serious cause of lower leg ulceration.